Effect of sacubitril/valsartan on the occurrence of cardiac arrhythmias and the risk of sudden cardiac death in heart failure: A meta-analysis of randomized controlled trials - Liu, Xue-Hui; Wang, Guan-Ling; Xu, Qiang; Zhang, Lei; Liu, Hong-Jun (Frontiers in Cardiovascular Medicine, 2022)
Background: Sacubitril/valsartan therapy reduced the risks of death and of hospitalization for heart failure (HF). HF and cardiac arrhythmias have shared physiological mechanisms. Therefore, sacubitril/valsartan may exhibit anti-arrhythmic properties in HF. The purpose of this study was to evaluate the effect of sacubitril/valsartan on the occurrence of cardiac arrhythmias and the risk of sudden cardiac death (SCD) in HF. Methods: We searched PubMed and Embase. Two independent authors identified randomized control trials (RCTs) that compared sacubitril/valsartan with placebo or active control in patients with HF. Primary outcomes were the occurrence of atrial arrhythmias, ventricular arrhythmias, and SCD. Risk ratios (RRs) with 95% confidence intervals (CIs) were pooled using a random-effects model for meta-analysis. Results: We included 9 RCTs with 18,500 patients (9,244 sacubitril/valsartan vs. 9,256 active control). Follow-up ranged from 2 to 35 months. The cumulative occurrence of events was 76, 13, and 48 per 1000 patient-years for atrial arrhythmias, ventricular arrhythmias and SCD, respectively. There was no significant association between sacubitril/valsartan therapy and the occurrence of atrial arrhythmias (RR 1.06; 95% CI: 0.97–1.17; P = 0.19) and ventricular arrhythmias (RR 0.86; 95% CI 0.68-1.10; P = 0.24). However, sacubitril/valsartan therapy significantly reduced the risk of SCD (RR 0.79; 95% CI 0.70-0.90; P = 0.03) compared with control. Conclusions: No association between sacubitril/valsartan therapy and the occurrence of atrial and ventricular arrhythmias was found, but sacubitril/valsartan therapy significantly reduced the risk of SCD.